DESIGN OF INTERACTIVE MULTIMEDIA AND BOOKLET WITHINFOGRAPHIC METODE AS SOCIALIZATION MEDIA ABOUT HANDLING PLASTIC WASTE BY DINAS LINGKUNGAN HIDUP KOTA SEMARANG - Nurhasbiansah, Albar (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2018)
Various kinds of pollution caused by plastic waste, one of them is the smoke from burning household-type plastic waste containing carcinogens. This happened because of the ignorance of the community about the impact arising from the burning of plastic waste. In this case, the Semarang City Environmental Service annually provides initialization related to the handling of plastic waste to increase public awareness, especially the people of Semarang city. The Semarang City Environmental Service needs interactive multimedia and booklets as a medium for socializing the handling of plastic waste. Thus the purpose of this study project is to produce a media for socializing plastic waste handling in the form of intaractive multimedia and a booklet with an infographic approach. The process of making works through several stages, starting from the stages of media research and analysis, the stage of determining goals and concepts, the production stage and the post-production stage. This study project has produced a medium of socialization in the form of interactive multimedia with 13 display interfaces with 1200 x 675 pixel resolution and booklet with 20 pages and 1 booklet cover measuring 15cm x 15cm.